Analysis of Planning to Increase the Coverage of Traindispatching Signals on the Line Divre III Palembang - Rissa Tukiman Lisyani (Jurnal Teknik Transportasi, 2025)
PT Kereta Api Indonesia (Persero) has set a target to increase coal transportation in South Sumatra to 105.2 MTPA. To support this target, improvements in railway operational facilities are required by enhancing the train dispatching coverage area. This enhancement aims to improve operational safety and address blank spots caused by mountainous terrain. This study discusses the improvement of train dispatching signal coverage on the Divre III Palembang line using a qualitative method with a descriptive explanation level. The study aims to plan the addition of base stations. The research results, using the RadioPlanner application for simulation, show that adding base stations can address blank spots and improve communication difficulties.